ANTIMICROBIAL, PHYTOCHEMICAL AND QUANTITATIVE HPLC ANALYSIS OF Moringa oleifera ROOT - Ramesh, Caroline Jeba (Innoriginal: International Journal of Sciences, 2018)
Objective:Â Phytochemical, in-vitro antibacterial activity, qualitative and quantitative phytochemical analysis of Moringa oleifera, belonging to family Moringaceae was taken to identify active compound. Methods: Dried root powder was extracted with ethanol and subjected to phytochemical analysis and identified phytoconstituents by HPLC and also using standards Gallic acids, benzoic acids, quercetin as well as their antimicrobial activity was tested on Escherichia coli and Staphylococcus.aureus. Results: Moringa oleifera root extract (ethanolic) showed antimicrobial activity against Escherichia .coli and Staphylococcus aureus. Qualitative and quantitative analysis detects the presence of phenolic compounds and flavonoids which confers the bioactivity to the extract. Conclusion:Â From the studies, we conclude that ethanol extract of Moringa oleifera root showed evidence that it could be a good therapeutic agent Key words: Moringa oleifera, HPLC, antimicrobial activity, the phytochemical analysis.